The Need for Research in Pregnant and Lactating Women. Issue 4 (July 2018) - Spatz, Diane L.
Abstract : Our breastfeeding expert, Dr. Spatz, is a member of the Task Force on Research Specific to Pregnant Women and Lactating Women which was established to advise the United States Secretary of Health and Human Services on current gaps in research for pregnant and lactating women. She shares her thoughts on this important topic.